Binge-Watching & Beyond: Navigating the Educational Landscape of Netflix - Abeda Shaikh, Vaishali Kothiya, Darshan Joshi, Khushboo Mishra (European Economic Letters (EEL), 2024)
This research investigates the effects of binge-watching web series on students, with a primary focus on Netflix content. The study delves into the psychological consequences of binge-watching, encompassing both positive intellectual engagement and potential negative outcomes such as shortened attention spans and academic performance issues. Employing a descriptive and analytical research design, the research combines primary data from surveys and secondary data from literature sources. Statistical methods including ANOVA, t-tests, and chi-square are employed to analyze patterns and relationships within the dataset. The outcomes underscore the substantial impact of binge-watching addiction on students' academic pursuits, relationships, and daily routines. The study highlights the importance of comprehending the psychological dimensions of binge-watching and advocates for a balanced approach to consuming web series content.